2020
DOI: 10.5344/ajev.2020.20012
|View full text |Cite
|
Sign up to set email alerts
|

Compost Application to Degraded Vineyard Soils: Effect on Soil Chemistry, Fertility, and Vine Performance

Abstract: A two-year experiment investigated the effects of compost application rate on soil chemical properties, vine nutrient status, vine performance, and grape juice characteristics in a degraded vineyard soil in northern California. The intent of the research was to identify vineyard management strategies to improve soil fertility and to identify optimal compost application rates. We applied composted steer manure at three rates (11.2, 22.4, 33.6 t/ha) in a randomized complete block design before the 2012 growing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 31 publications
(46 reference statements)
4
7
1
Order By: Relevance
“…Observing the musts quality parameters, the occurrence of a delay in maturation for the plants treated with soil improvers could be assumed. This is in agreement with the vegetative data results, and in according to recent work with compost [8].…”
Section: Fig 1 Biological Quality Of the Soil Expressed With Comparative Diagnostics Between Average Values Of The Blocks And Ideal Valuesupporting
confidence: 94%
“…Observing the musts quality parameters, the occurrence of a delay in maturation for the plants treated with soil improvers could be assumed. This is in agreement with the vegetative data results, and in according to recent work with compost [8].…”
Section: Fig 1 Biological Quality Of the Soil Expressed With Comparative Diagnostics Between Average Values Of The Blocks And Ideal Valuesupporting
confidence: 94%
“…The treatments were applied in autumn 2017 and autumn 2018 with a manure spreader machine. Compost was applied on a per hectare basis, with a single application in bands that were lightly incorporated (10–20 cm) into the soil directly under the interrow (Wilson et al ., 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Four soil treatments were applied (three compost The treatments were applied in autumn 2017 and autumn 2018 with a manure spreader machine. Compost was applied on a per hectare basis, with a single application in bands that were lightly incorporated (10-20 cm) into the soil directly under the interrow (Wilson et al, 2021). At the composting Center of Faltona (Alia Servizi Ambientali SpA, Borgo San Lorenzo, Italy), with the technical and scientific supervision of the Agricultural School (DAGRI, University of Florence, Italy), in a specially set up area tests were carried out to obtain quality compost, derived from organic waste matrices selected from separate collection from MSW, agri-food waste, etc.…”
Section: Temperature Experiments Location and Compost Analysismentioning
confidence: 99%
“…So far, results of different studies are contradictory. While beneficial effects of OA incorporation on parameters such as vegetative growth or yield could be shown in some studies (Genesio et al, 2015;Gaiotti et al, 2017;Tangolar et al, 2020;Marıń-Martıńez et al, 2021;Wilson et al, 2021), others reported no or only negligible influence on grapevine performance (Mugnai et al, 2012;Schmidt et al, 2014;Baldi et al, 2022). Some studies reported even negative effects on grape quality parameters (e.g., Gaiotti et al, 2017;Botelho et al, 2021).…”
Section: Introductionmentioning
confidence: 99%